1996
DOI: 10.1177/1075547096018002004
|View full text |Cite
|
Sign up to set email alerts
|

Newspaper Coverage of the Coronary Artery Bypass Grafting Report

Abstract: The accuracy of medical stories in newspapers is a controversial issue. This study evaluated the accuracy of newspaper reports on an annual consumer report that reports the expected number of deaths following bypass surgery conducted in Pennsylvania hospitals. Analysis of 42 articles published following the 1994 report identified 52 factual errors, 127 mistakes in technical terms, 29 misspellings of proper names, and 7 misquotations. Daily newspapers averaged 5.61 errors per article, weekly newspapers averaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Friends and family were the least frequently reported information source across content categories. The reliance on the mass media for heart-relevant information (in particular, for such speci c information as personal AMI risk pro le) is a potential problem since the mass media have been criticized for disseminating incomplete and/or inaccurate health information (Ankney, Heilman, & Kolff, 1996;Molitor, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Friends and family were the least frequently reported information source across content categories. The reliance on the mass media for heart-relevant information (in particular, for such speci c information as personal AMI risk pro le) is a potential problem since the mass media have been criticized for disseminating incomplete and/or inaccurate health information (Ankney, Heilman, & Kolff, 1996;Molitor, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, no matter what kind of science coverage is published, the reality as constructed in the mass media differs from science's viewpoint. A long research tradition has described the 'biases' of the media's science coverage, for example, by asking scientists to evaluate the precision of media reports, which in practically all cases finds inaccuracies: Ankney et al (1996), for example, found some 220 factual and terminological errors in 42 newspaper articles on medicine (cf. Bell 1994;Oxman et al 1993;Roche and Muskavitch 2003).…”
Section: How Science Is Presented In the Media: Characteristics Of Comentioning
confidence: 99%
“…Accuracy in media coverage has been discussed as a very important matter [7]. At the time of an incident, initially there is much coverage while the incident attracts public attention.…”
Section: Introductionmentioning
confidence: 99%